Treatment of biliodigestive anastomotic strictures after transplantation of left lateral segment of the liver - A. R. Monakhov; B. L. Mironkov; M. A. Voskanov; S. V. Meshcheryakov; E. T. Azoev; K. O. Semash; T. A. Dzhanbekov; O. V. Silina; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2020)
Many studies have shown that biliary complications after transplantation of the left lateral segment (LLS) of the liver reduce graft and recipient survival. Thus, timely correction of biliary complications, and strictures in particular, improves long-term outcomes in transplantation. Objective: to analyze our own experience in correcting biliary strictures in LLS graft transplantation. Materials and methods. From February 2014 to April 2020, 425 LLS grafts were transplanted in children. 19 (4.5%) patients were diagnosed with biliary strictures at different times after transplantation (from 0.2 to 97 months). Results. Biliary strictures were more often formed a year after transplantation (17.8 ± 23.9 months). In 14 out of the 19 patients, internal-external biliary drainage was successfully performed with phased replacement of the catheter with one that was larger in diameter (from 8.5 Fr to 14 Fr). The catheters were removed in 8 patients after completion of the treatment cycle. Restenosis was not observed during follow-up (13 ± 8.7 months) after the internal-external biliary drainage catheter had been removed. In 5 cases, antegrade passage of a guide wire through the stricture was unsuccessful. As a result, biliary reconstruction was performed in 4 (21.1%) patients and retransplantation was required in 1 (5.3%) patient. Conclusion. An antegrade minimally invasive approach can successfully eliminate biliary strictures in most children after liver LLS graft transplantation. The proposed technique is effective and safe.